Nonfirmands: Danish youth who choose not to have a Lutheran confirmation. Issue 1 (2nd January 2018) - Kasselstrand, Isabella; Zuckerman, Phil; Little, Robert; Westbrook, Donald A.
Abstract: Most Danish youth participate in the traditional Lutheran ritual of confirmation. However, a growing minority does not. Based on survey data collected in 2011 from over 600 Danish pupils, this study examines the ways in which Danish 'nonfirmands' are different from their peers who participate in confirmation in relation to religious background, personal religious beliefs, intellectual engagement, and demographic factors. We further explore key motivations for 'nonfirmation' expressed by the nonfirmands in the sample. Broadly speaking, our findings highlight secular socialization and individual beliefs about God as key elements in understanding the nonfirmand and his or her reasons for opting out of confirmation. We expect confirmations to continue to decline in popularity as nonfirmation gains social acceptance, as nonfirmands raise their own children, and as Denmark becomes increasingly secular.